Exporting data from an openEHR repository to standard formats - Almeida, Jorge Daniel Borges Brilhante (2015)
With the healthcare sector computerization, a large amount of data is produced from medical encounters, therapeutic outcomes and other aspects of healthcare provider’s organizations current activity. Decision support systems cover several methodologies and approaches that may be applied to the healthcare sector and, since that they store and analyze data in a tabular format, it becomes necessary to assure that data sources with different data representations can be used to feed these systems. The present work focuses on the development of a methodology to export data from an openEHR repository to standard formats through a software tool which adapts itself to different data sources for later exploration in statistical and decision support systems. From use case and requirements analysis to the efective development of the tool, several steps were performed to document progress and to ground conclusions regarding operational test data. Obtained results indicate that this data export is feasible, but also highlight the need to define parameters so that the tool may function.